Reproductive plasticity of Hawaiian Montipora corals following thermal stress - E. Michael Henley (Nature Portfolio, 2021)
Abstract Ocean warming, fueled by climate change, is the primary cause of coral bleaching events which are predicted to increase in frequency. Bleaching is generally damaging to coral reproduction, can be exacerbated by concomitant stressors like ultraviolet radiation (UVR), and can have lasting impacts to successful reproduction and potential adaptation. We compared morphological and physiological reproductive metrics (e.g., sperm motility, mitochondrial membrane integrity, egg volume, gametes per bundle, and fertilization and settlement success) of two Hawaiian Montipora corals after consecutive bleaching events in 2014 and 2015. Between the species, sperm motility and mitochondrial membrane potential had the most disparate results. Percent sperm motility in M. capitata, which declined to ~ 40% during bleaching from a normal range of 70–90%, was still less than 50% motile in 2017 and 2018 and had not fully recovered in 2019 (63% motile). By contrast, percent sperm motility in Montipora spp. was 86% and 74% in 2018 and 2019, respectively. This reduction in motility was correlated with damage to mitochondria in M. capitata but not Montipora spp. A major difference between these species is the physiological foundation of their UVR protection, and we hypothesize that UVR protective mechanisms inherent in Montipora spp. mitigate this reproductive damage.